Intraocular Pressure Fluctuation after Cataract Surgery: Comparison between Phacoemulsification & Small-Incision Cataract Surgery - Banu Aji Dibyasakti; Suhardjo Suhardjo (Majalah Oftalmologi Indonesia, 2016)
Background: To measure and compare intraocular pressure (IOP) fluctuation before & after cataractsurgery with phacoemulsification & small-incision cataract surgery (SICS) in a mass cataract surgeryheld by Departemen of Ophthalmology, Faculty of Medicine, Universitas Gadjah Mada â€“ SardjitoHospital.Methods: This is a cohort study involving 100 eyes from 100 age-related cataract patients who underwentnon-complicated cataract surgery (been done by multiple surgeons, including senior ophthalmologists,fellowships, and residents). The subject were divided into 2 groups: 37 patients were performed withphacoemulsification & 63 with SICS. IOP fluctuation (before, day 2, 5, & 28 after cataract surgery)was measured by using non-contact tonometry. The incidence of high IOP (>22 mmHg) between twomethods were compared respectively by using chi-square analysis.Results: The mean IOP for phacoemulsification were: 14 (before), 12.83 (day 2), 13.7 (day 5), 12.45(day 28); while SICS were: 14.13 (before), 17.32 (day 2), 11.40 (day 5), 10.39 (day 28). The incidence ofhigh IOP for phacoemulsification were: 4.2% (day 2), 4.3% (day 5), 0% (day 28); while SICS were: 22.7%(day 2), 5.9% (day 5), 0% (day 28). We found statistically significant difference in the incidence of highIOP between two methods on day 2 after cataract surgery (p=0.047) and no statistically significantdifference on day 5 (p=0.799).Conclusion: Phacoemulsification gives more stable IOP fluctuation than SICS. There is IOP spikes onday 2 after SICS.Â Keywords: cataract, phacoemulsification, small-incision cataract surgery, high intraocular pressure